Innovative-Entrepreneurial Competence as Result of Training the Effective Manager - T. Y. Tsibizova; N. L. Sokolova (Научный диалог, 2017)
The review of the monograph by V. V. Kolchina and M. G. Sergeyeva “Formation of Innovative-Entrepreneurial Competence of Students - Future Managers,” published in 2016, presents a brief annotation of studied by the authors scientific and practical problems of training a professional manager demanding in the labour market and able to effectively carry out professional activities.